FUNGSI POMABARI (GOTONG-ROYONG) PETANI KELAPA KOPRA DI DESA WASILEO KECAMATAN MABA UTARA KABUPATEN HALMAHERA TIMUR PROVINSI MALUKU UTARA - Pawane, Faisal S. (HOLISTIK, Journal Of Social and Culture, 2016)
Indonesia is a state consisting of motley the community, nations, ethnic or social group, religion, and culture of various from the one with other regions coloring variety of culture A reality cannot be denied is ever happened a number of conflicts in various areas. Some the conflict has its own genealogy and its anatomy. Was triggered the different ethnic and gap, religion, political, and other foult line (SARA) problems. The Sawai community most embraced the Christian faith, and there are Islamic. Awareness of the diversity of in turn bring up attitude tolerant and attitude open to the existence and the presence of ethnic other. The community Lelilef adheres to the principles of local knowledge, to want a life together in realizing atmosphere safe, peaceful, from harmonious in the community. Philosophy fagogoru which means ngakure ra sai (fraternity), budi re bahasa (reason and language), sopan re hormat (polite and respect) timtat re mimoi (fear and shame). Therefore, this is being ground or foundation for the Lelilef to keep religious life, so they always live in climate safe, peace and prosperity (legae santuli). There are three factors for people who live in the Lelilef village in District Weda Tengah in social life the environmental factors, the historical, the language and another factor is religion and politics. Keywords: conflict, harmonious, tolerant.